Adsorption column filler and application thereof

By combining the pore-shaped gel-type resin with functionalized magnetic beads to form efficient adsorption column fillers, the problem of difficulty in separating and treating harmful substances in cerebrospinal fluid in the prior art is solved, effectively retaining and recycling cerebrospinal fluid components is achieved, and the treatment effect is improved.

CN119869477AInactive Publication Date: 2025-04-25徐霖南
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510109785.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult to effectively separate and treat harmful substances in cerebrospinal fluid, and it is difficult to maintain the original proportion of cerebrospinal fluid components, affecting the therapeutic effect.

Method used

Adsorption column filler composed of resin and magnetic beads are used to combine the pore-shaped resin with functional magnetic beads through oscillation chimeric technology to form efficient filler to achieve separation of harmful substances in cerebrospinal fluid and retain the original proportion of cerebrospinal fluid components.

Benefits of technology

It has achieved effective disposal of harmful protein components in cerebrospinal fluid, retained beneficial components, and retained the original ratio of cerebrospinal fluid components. It is similar to healthy cerebrospinal fluid, which can be directly recycled and improved the therapeutic effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869477A_ABST
    Figure CN119869477A_ABST
Patent Text Reader

Abstract

The invention discloses an adsorption column filler and application thereof, by improving a common adsorption column filler, the adsorption column filler which is rare in the market, has important application requirements and aims at screening cerebrospinal fluid is obtained, IL-6, TNF-alpha, TGF-beta1, GFAP, IL-1beta, S100beta, MMP-9, BDNF, NGF and NT-3 can be separated, other harmful substances are not introduced, and the adsorption column filler has the advantages that the adsorption column filler can be applied to screening of cerebrospinal fluid; the ratio of the original components of the cerebrospinal fluid is reserved, and the adsorption column filler has a good prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of filler synthesis and application, and in particular relates to an adsorption column filler and application thereof. Background Art

[0002] Adsorption columns are widely used in many fields, mainly including environmental protection, industrial production, medical equipment, food industry and biomedicine. Among them, in the field of biomedicine, adsorption columns are widely used because of their high efficiency, convenience and safety, such as the following scenarios: critical care, liver function auxiliary treatment, sepsis treatment, etc. In critical care, the blood is generally purified to remove inflammatory factors and toxins in the blood, eliminate systemic inflammatory reactions, and improve the treatment effect. Most adsorption columns on the market are used for blood purification. One of the more typical medical scenarios for blood purification is to dialyze the blood of kidney patients to remove toxins and water and replace part of the kidney function. With the advancement of medical technology and the variability of human diseases, the functions of blood-type adsorption columns are gradually unable to meet the above situations. Therefore, more types of adsorption columns are needed for different medical scenarios.

[0003] Cerebrospinal fluid is a colorless and transparent liquid that exists in the ventricles and subarachnoid space. It has a specific gravity of 1.005, a total volume of 130 to 150 ml, and an average daily production of 524 ml. Cerebrospinal fluid surrounds and supports the entire brain and spinal cord, effectively reducing the weight of the brain to 1 / 6, and plays a certain protective role against trauma. In terms of clearing metabolic products and inflammatory exudates, it plays the role of lymph fluid in other parts of the body. Therefore, cerebrospinal fluid is very important to the safety of the entire internal structure of the human skull, which also means that it is very important to humans.

[0004] The main components of the brain include water, inorganic matter, organic matter and cells, among which water has the highest content, accounting for about 99%; inorganic matter is mainly some inorganic ions, including sodium ions (Na + ), potassium ion (K + ), calcium ions (Ca 2+ ) and magnesium ions (Mg 2+ ) etc.; also contains proteins, glucose and some metabolites; only a very small number of cells, mainly lymphocytes. Among them, proteins mainly include some albumin and globulin;

[0005] Adsorption columns for hemodialysis have been developed in large quantities due to the large demand. Relatively speaking, cerebrospinal fluid dialysis is relatively new, so adsorption columns for this type of dialysis are a direction worthy of research. In adsorption columns, the main role played by the configuration is not only the filler, but also the purification ability of the filler can be improved by means of modification, grafting, and the introduction of functional bonds. Therefore, the research on adsorption column fillers for separating harmful substances in cerebrospinal fluid is a good direction. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides an adsorption column filler and application thereof.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] An adsorption column filler, composed of resin and magnetic beads, is characterized in that the main body of the filler is a porous gel-type resin, the magnetic beads are micron-level functionalized magnetic beads, and the porous gel-type resin and the magnetic beads are integrated by vibration.

[0009] By adopting the above technical scheme, the present invention flexibly combines the resin and the magnetic beads, and uses two purification methods with single functionality together. In the above technical scheme, the resin is embedded with the magnetic beads, the loading amount is variable and controllable, the range of use scenarios is expanded, the loading by shaking is simple and convenient, and the resin state can be activated during the shaking process.

[0010] And in the non-working state, after the gel-type resin is formed, it goes through a drying process to stabilize the pores therein, and the supercritical drying method can prevent the gel from shrinking and the pores from collapsing, thereby maintaining the porous structure of the aerogel. In actual use, it only needs to be activated by the water phase, which can be carried out synchronously during the shock loading, which not only maintains the moist state of the filler but also facilitates the integration of the resin and the magnetic beads.

[0011] Preferably, the gel-type resin is composed of a liquid resin and a curing agent, and the liquid resin is at least one of an epoxy resin, a polyurethane resin or a polyester resin.

[0012] Furthermore, the liquid resin is an epoxy resin.

[0013] By adopting the above technical solution, the gel-type resin composed of epoxy resin and curing agent has better adhesion than other types of resins, and is also advantageous in terms of stability after embedding. Moreover, such gel-type resin has better retention of specific target screening substances.

[0014] Preferably, the pores of the gel-type resin are 50 to 80 μm.

[0015] Preferably, the particle size of the magnetic beads is 50 to 80 μm.

[0016] Preferably, the magnetic beads are modified and carboxylated to form functionalized magnetic beads.

[0017] Preferably, the carboxylation treatment is obtained by a mixed reaction of an aqueous phase solution, an oil phase solution and other reagents.

[0018] By adopting the above technical solution, the treated magnetic beads can capture more effectively, so as to purify the target substances, and the processing volume will be larger.

[0019] Preferably, the aqueous phase solution is anhydrous ethanol and deionized water, the oil phase solution is styrene and acrylic acid, and the other reagents are emulsifiers and initiators.

[0020] Preferably, the modification treatment is to mix oleic acid, pteroic acid and alkyl lactic acid esters with micron-sized magnetic beads for modification treatment.

[0021] By adopting the above technical solution, the modified magnetic beads have a stronger retention of the target protein.

[0022] Preferably, the gel-type resin is grafted, and the grafted monomer is one of diethyl maleate and dibutyl maleate.

[0023] By adopting the above technical scheme, both magnetic beads and resin can more effectively treat the target adsorbent. In addition, the combination of resin and magnetic beads not only works synergistically during actual treatment, but also facilitates the reduction treatment of the entire filler after treatment, so as to better recycle the use without affecting the use effect and treatment efficiency.

[0024] In order to solve the above technical problems, the present invention also provides an application of an adsorption column filler, especially an application in screening cerebrospinal fluid components for non-diagnostic or therapeutic purposes.

[0025] Beneficial effects of the present invention:

[0026] 1) It can specifically treat harmful protein components in cerebrospinal fluid and retain beneficial components;

[0027] 2) The original ratio of the components in the cerebrospinal fluid is retained, which is similar to or close to healthy cerebrospinal fluid and can be recycled without additional treatment;

[0028] 3) The preparation method of the filler is simple, easy to use, and has a promising prospect.

[0029] The present invention improves a general adsorption column filler to obtain an adsorption column filler for cerebrospinal fluid screening which is rare in the market but has important application needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Figure 2 is a diagram of cerebrospinal fluid samples after the filler purification process in Examples 1, 2, 3 and 4. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0032] The raw materials, samples, reagents and equipment used in the tea beverage preparation process described in the embodiments of the present invention are all commercially available and can be purchased on the market.

[0033] The present invention is further described below by means of specific examples, but the scope of the present invention is not limited thereto.

[0034] Embodiment 1:

[0035] Preparation of gel-type resin: prepare epoxy resin, diethyl maleate, BDMA, and curing agent for grafting treatment: the mass ratio of epoxy resin and curing agent is 2:1, the amount of BDMA added is 0.2% of the mass of epoxy resin, and the amount of diethyl maleate added is 3%. All are mixed and stirred evenly with a stirring rod until the mixed liquid becomes smooth; the mixed liquid is placed in a curing furnace for gel treatment: first preheat the curing furnace to 60±5℃, then put the mold containing epoxy resin casting material into the curing furnace, then heat the curing furnace to 80℃ and keep it for 8 to 10 hours for gel treatment; finally, heat the curing furnace to 105℃, keep it for 2 hours, and then heat it to 130℃ and keep it for 8 to 10 hours for curing treatment. The cured resin stabilizes the pores through the drying process, and the supercritical drying method can prevent gel shrinkage and pore collapse, thereby maintaining the porous structure of the aerogel.

[0036] Synthesis of magnetic beads: Add ferric chloride hexahydrate and ferrous chloride tetrahydrate to deionized water, pass nitrogen to deoxygenate, then add ammonia water, react at 62°C for 3h, separate with a magnet, and wash to obtain ferrosoferric oxide nanoparticles. The amount of ferric chloride hexahydrate added is 0.8wt% of the deionized water, the amount of ferrous chloride tetrahydrate used is 47wt% of the ferric chloride hexahydrate, and the amount of ammonia water added is 4.2wt% of the deionized water.

[0037] Modified magnetic beads: The magnetic beads were dispersed in deionized water, ultrasonically dispersed to obtain a magnetic bead dispersion, deoxygenated by nitrogen, and oleic acid, pteroic acid and alkyl lactate were added at a temperature of 82°C. After reacting for 2 hours, the modified magnetic beads were washed and dried by nitrogen to obtain the modified magnetic beads. The content of magnetic beads in the magnetic bead dispersion was 0.8wt%, the amount of oleic acid added was 1.2wt% of the magnetic bead dispersion, the amount of pteroic acid added was 0.15wt% of the magnetic beads, and the amount of alkyl lactate added was 0.30wt% of the magnetic bead dispersion.

[0038] Carboxylation treatment: the modified magnetic beads are dispersed in an aqueous solution to obtain a magnetic fluid, and then an oil phase solution is added, polyoxyethylene fatty acid ester is added, ammonium persulfate is added, and the mixture is stirred and dispersed for 20 minutes. Under nitrogen protection, the mixture is reacted at a temperature of 80°C for 12 hours. After the reaction is completed, the mixture is magnetically separated and washed to obtain carboxylated magnetic beads. The aqueous solution includes anhydrous ethanol and deionized water, the content of anhydrous ethanol in the aqueous solution is 80wt%, and the amount of modified magnetic nanoparticles used is 20wt% of the aqueous solution; the oil phase solution includes styrene and acrylic acid, the content of styrene in the oil phase solution is 85wt%, and the content of acrylic acid in the oil phase solution is 12wt%; the amount of the oil phase solution used is 30wt% of the aqueous solution; the amount of the emulsifier used is 0.28wt% of the aqueous solution; and the amount of the initiator used is 0.8wt% of the oil phase solution.

[0039] Activate before use: put the dried resin and the treated functional magnetic beads into an ultrasonic instrument and add deionized water to shake them. The moistened gel-type resin can be well embedded in the functional magnetic beads.

[0040] Cerebrospinal fluid separation: The cerebrospinal fluid is poured into the adsorption column, and it flows through the entire filler column at a uniform speed through the filler and the negative pressure pump in the adsorption column. The adsorbed cerebrospinal fluid is collected for measurement, and it is found that the content of IL-6, TNF-α, TGF-β1, GFAP, IL-1β, S100β, MMP-9, etc. in the cerebrospinal fluid is negligible; while BDNF, NGF, and NT-3 still exist, and there is little water loss and no other substances are introduced; the original ratio of the components in the cerebrospinal fluid is retained, which is similar to or close to healthy cerebrospinal fluid and can be directly recycled.

[0041] Embodiment 2:

[0042] Preparation of gel-type resin: prepare epoxy resin, diethyl maleate, BDMA, and curing agent for grafting treatment: epoxy resin and curing agent, the mass ratio is 2:1, the amount of BDMA added is 0.2% of the mass of epoxy resin, and the amount of dibutyl maleate added is 3%. All are mixed and stirred evenly with a stirring rod until the mixed liquid becomes smooth; the mixed liquid is placed in a curing furnace for gel treatment: first preheat the curing furnace to 65°C, then put the mold containing the epoxy resin casting material into the curing furnace, then heat the curing furnace to 82°C and keep it for 9 hours for gel treatment; finally, heat the curing furnace to 105°C, keep it for 2 hours, and then heat it to 135°C and keep it for 8 hours for curing treatment. The cured resin stabilizes the pores through the drying process, and the supercritical drying method can prevent gel shrinkage and pore collapse, thereby maintaining the porous structure of the aerogel.

[0043] Synthesis of magnetic beads: Add ferric chloride hexahydrate and ferrous chloride tetrahydrate to deionized water, pass nitrogen to deoxygenate, then add ammonia water, react at 62°C for 3h, separate with a magnet, and wash to obtain ferrosoferric oxide nanoparticles. The amount of ferric chloride hexahydrate added is 0.8wt% of the deionized water, the amount of ferrous chloride tetrahydrate used is 47wt% of the ferric chloride hexahydrate, and the amount of ammonia water added is 4.2wt% of the deionized water.

[0044] Modified magnetic beads: The magnetic beads were dispersed in deionized water, ultrasonically dispersed to obtain a magnetic bead dispersion, deoxygenated by nitrogen, and oleic acid, pteroic acid and alkyl lactate were added at a temperature of 82°C. After reacting for 2 hours, the modified magnetic beads were washed and dried by nitrogen to obtain the modified magnetic beads. The content of magnetic beads in the magnetic bead dispersion was 0.8wt%, the amount of oleic acid added was 1.2wt% of the magnetic bead dispersion, the amount of pteroic acid added was 0.15wt% of the magnetic beads, and the amount of alkyl lactate added was 0.30wt% of the magnetic bead dispersion.

[0045] Carboxylation treatment: the modified magnetic beads are dispersed in an aqueous solution to obtain a magnetic fluid, and then an oil phase solution is added, SDS is added, sodium persulfate is added, and the mixture is stirred and dispersed for 10 minutes. Under nitrogen protection, the mixture is reacted at a temperature of 80°C for 12 hours. After the reaction is completed, the mixture is magnetically separated and washed to obtain carboxylated magnetic beads. The aqueous solution includes anhydrous ethanol and deionized water, the content of anhydrous ethanol in the aqueous solution is 80wt%, and the amount of modified magnetic nanoparticles used is 20wt% of the aqueous solution; the oil phase solution includes styrene and acrylic acid, the content of styrene in the oil phase solution is 85wt%, and the content of acrylic acid in the oil phase solution is 12wt%; the amount of the oil phase solution used is 30wt% of the aqueous solution; the amount of the emulsifier used is 0.28wt% of the aqueous solution; and the amount of the initiator used is 0.8wt% of the oil phase solution.

[0046] Activate before use: put the dried resin and the treated functional magnetic beads into an ultrasonic instrument and add deionized water to shake them. The moistened gel-type resin can be well embedded in the functional magnetic beads.

[0047] Cerebrospinal fluid separation: The cerebrospinal fluid is poured into the adsorption column, and the fluid flows through the entire column at a uniform speed through the filler and the negative pressure pump. The adsorbed cerebrospinal fluid is collected for measurement, and it is found that the content of IL-6, TNF-α, TGF-β1, GFAP, IL-1β, S100β, MMP-9, etc. in the cerebrospinal fluid is negligible; while BDNF, NGF, and NT-3 still exist, and there is little water loss and no other substances are introduced; the original ratio of the components in the cerebrospinal fluid is retained, which is similar to or close to healthy cerebrospinal fluid and can be directly recycled.

[0048] Embodiment 3:

[0049] The epoxy resin in Example 1 is replaced with a polyurethane resin, and the rest remains unchanged;

[0050] After the filler is adsorbed, the contents of IL-6, TNF-α, TGF-β1, GFAP, IL-1β, S100β, MMP-9, etc. in the cerebrospinal fluid are negligible; while BDNF, NGF, and NT-3 still exist, and there is little water loss and no other substances are introduced.

[0051] Embodiment 4:

[0052] The epoxy resin in Example 2 is replaced with a polyester resin, and the rest remains unchanged;

[0053] Cerebrospinal fluid separation: The cerebrospinal fluid is poured into the adsorption column, and the fluid flows through the entire column at a uniform speed through the filler and the negative pressure pump. The adsorbed cerebrospinal fluid is collected for measurement, and it is found that the content of IL-6, TNF-α, TGF-β1, GFAP, IL-1β, S100β, MMP-9, etc. in the cerebrospinal fluid is negligible; while BDNF, NGF, and NT-3 still exist.

[0054] The results of Examples 1 to 4 are shown in the attached Figure 1 It was verified that the present invention provides a filler that can effectively separate components in cerebrospinal fluid, without losing the original cerebrospinal fluid component ratio and without introducing other substances, with high separation efficiency and good separation effect.

Claims

1. An adsorption column filler, composed of resin and magnetic beads, characterized in that: The main body of the filler is a gel-type resin with pores, the magnetic beads are micron-level functionalized magnetic beads, and the gel-type resin with pores and the magnetic beads are integrated through vibration.

2. The adsorption column packing according to claim 1, characterized in that: The gel-type resin is composed of a liquid resin and a curing agent, wherein the liquid resin is at least one of an epoxy resin, a polyurethane resin or a polyester resin.

3. The adsorption column packing according to claim 2, characterized in that: The pores of the gel-type resin are 50 to 80 μm.

4. The adsorption column packing according to claim 1, characterized in that: The particle size of the magnetic beads is 50 to 80 μm.

5. The adsorption column packing according to claim 4, characterized in that: The magnetic beads are modified and carboxylated to form functionalized magnetic beads.

6. The adsorption column packing according to claim 5, characterized in that: The carboxylation treatment is obtained by mixing and reacting an aqueous phase solution, an oil phase solution and other reagents.

7. The adsorption column packing according to claim 6, characterized in that: The aqueous phase solution is anhydrous ethanol and deionized water, the oil phase solution is styrene and acrylic acid, and the other reagents are emulsifiers and initiators.

8. The adsorption column packing according to claim 5, characterized in that: The modification treatment is obtained by mixing oleic acid, pteroic acid and alkyl lactic acid ester with micron-sized magnetic beads.

9. The adsorption column packing according to claim 2, characterized in that: The gel-type resin is grafted, and the grafted monomer is one of diethyl maleate and dibutyl maleate.

10. The use of an adsorption column filler according to any one of claims 1 to 9, characterized in that: Use of the filler in screening cerebrospinal fluid components for non-diagnostic or therapeutic purposes.